Fluoxetine Administration in Juvenile Monkeys: Implications for Pharmacotherapy in Children - Golub, Mari S.; Hogrefe, Casey E.; Sherwood, Richard J.; Turck, Christoph W. (Frontiers in Pediatrics, 2018)
Fluoxetine therapy has been approved for children with Major Depressive Disorder and Obsessive Compulsive Disorder for over 14 years and has expanded to other childhood behavior disorders. As use increases, more detail on fluoxetine effects during juvenile brain development can help maintain safe and effective use of this therapy. Here, a narrative review is provided of previously published findings from a large nonhuman primate project. Fluoxetine was administered to juvenile male rhesus monkeys for an extended period (two years) prior to puberty. Compared to controls, treated monkeys showed sleep disruption, facilitated social interaction, greater impulsivity, and impaired sustained attention during treatment. No effects on growth were seen. Metabolomics assays characterized a distinctive response to fluoxetine and demonstrated individual differences that were related to the impulsivity measure. Fluoxetine interactions with MAOA polymorphisms that influenced behavior and metabolomics markers were an important, previously unrecognized finding of our studies. After treatment was discontinued, some behavioral effects persisted, but short term memory and cognitive flexibility testing did not show drug effects. This detailed experimental work can contribute to clinical research and continued safe and effective fluoxetine pharmacotherapy in children.